2001
DOI: 10.1002/ana.10053
|View full text |Cite
|
Sign up to set email alerts
|

Park6‐linked parkinsonism occurs in several european families

Abstract: The Parkin gene on 6q25.2-27 is responsible for about 50% of autosomal recessive juvenile parkinsonism and less than 20% of sporadic early-onset cases. We recently mapped a novel locus for early-onset parkinsonism (PARK6) on chromosome 1p35-p36 in a large family from Sicily. We now confirm linkage to PARK6 in eight additional families with Parkin-negative autosomal recessive juvenile parkinsonism from four different European countries. The maximum cumulative pairwise LOD score was 5.39 for marker D1S478. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 17 publications
0
42
0
3
Order By: Relevance
“…Additional unrelated families with positive linkage to this region were described (Valente et al 2002), and mutations in the PINK1 gene were identified (Valente et al 2004a). Initial screens for PINK1 mutations in early-onset familial cases revealed a number of novel mutations; however, these mutations are less common than are alterations in the parkin gene in early-onset PD cases (Hatano et al 2004, Valente et al 2004b.…”
Section: Pink1 (Omim 608309; Park6; Pten-induced Putative Kinase 1)mentioning
confidence: 99%
“…Additional unrelated families with positive linkage to this region were described (Valente et al 2002), and mutations in the PINK1 gene were identified (Valente et al 2004a). Initial screens for PINK1 mutations in early-onset familial cases revealed a number of novel mutations; however, these mutations are less common than are alterations in the parkin gene in early-onset PD cases (Hatano et al 2004, Valente et al 2004b.…”
Section: Pink1 (Omim 608309; Park6; Pten-induced Putative Kinase 1)mentioning
confidence: 99%
“…PARK6 (gene PINK1, PTEN-induced putative kinase 1): It is characterized by early onset in most patients (mean age at onset in the 30s, ranging from childhood until the seventh decade of life), dystonia at onset or symptom symmetry in some cases, slow disease progression, excellent levodopa responsiveness, early peak-dose dyskinesias; hyperreflexia has been described; rare cases with very early onset display sleep benefit and diurnal fluctuations (Valente et al 2001(Valente et al , 2002Bonifati 2005;Ibáñez et al 2006;Leutenegger et al 2006). Psychiatric disturbances such as depression, anxiety, and psychosis are a frequent finding (Bonifati 2005;Ibáñez et al 2006;Steinlechner et al 2007).…”
Section: Clinical Approach To Parkinson's Diseasementioning
confidence: 99%
“…9 In PARK6-linked parkinsonism, symptoms often reported in patients with early-onset autosomal-recessive parkinsonism, such as early dystonia and sleep benefit, were not observed. 10 We recently mapped a third locus (PARK7) in a consanguineous pedigree with early-onset autosomal recessive parkinsonism. 11 The PARK7 critical region lies on chromosome 1p36, and is clearly separated from PARK6 by 25 cM.…”
mentioning
confidence: 99%